FRI0231 Treatment with BI 655064 (Antagonistic Anti-CD40 Antibody) Modulates Biomarkers Associated with Rheumatoid Arthritis (RA). (15th July 2016) - Visvanathan, S.; Ramanujam, M.; Schoelch, C.; Vinisko, R.; Mueller-Ladner, U.; Padula, S.; Fine, J.S.; Steffgen, J.
Abstract : Background: Co-stimulation through the CD40- CD40L axis has been implicated in the pathogenesis of RA including T cell mediated responses, B cell driven autoantibodies, adhesion molecule expression, synovial hyperplasia, and pannus formation, in addition to the secretion of proinflammatory cytokines and MMPs. Circulating CD40L levels are elevated in RA patients versus healthy controls. BI 655064 is a humanized antagonistic anti-CD40 monoclonal antibody which blocks the CD40/ CD40L interaction in in vitro CD40L induced B cell and APC activation assays with IC50 of <1nM. Objectives: To characterize the effect of BI 655064 on cellular and protein biomarkers in RA patients with prior inadequate response to a stable dose MTX ≥15 mg over a 12 wk period of treatment. Methods: In this double-blinded, randomized trial RA patients were treated with either 120 mg BI 655064 or placebo q1w for 12 wks as add-on to MTX. Inclusion criteria were ≥6 swollen and ≥6 tender joints, CRP >8 mg/L or ESR>28 mm/1h. The primary efficacy endpoint was ACR20 response at wk 12.Select biomarkers were assessed in whole blood and serum pre and post treatment with BI 655064. Results: Treatment with BI 655064 resulted in minimal changes in median %CD19+ B cell population but larger median decreases in select %CD95+ activated B cell subsets, specifically class switched (CD19+IgD-CD27+CD95+), pre-switched (CD19+IgD+CD27+CD95+) and double negative (CD19+IgD-CD27-CD95+) cells and decreases in autoantibodies (IgG-RF and IgA-RF), total IgG and IgM levels in RA patients vs placebo at 12 wks. Median decreases in IL-6 levels (important for B cell and monocyte differentiation) and select bone resorption biomarkers (MMP-3 and RANKL) were also observed in the BI 655064 treated patients vs placebo through 12 wks. Baseline levels of IgG RF, IgM RF, TNFa and COMP correlated with improvement in swollen joint counts at 12 wks and IgA RF levels correlated with improvement in DAS-28 CRP scores at 12 wks in patients treated with BI 655064. Conclusions: These results demonstrate that treatment of RA patients with BI 655064 decreases activated B cell subsets, inhibits the production of pathogenic autoantibodies, and reduces the level of circulaiting inflammatory and bone resorption biomarkers at 12 wks. Baseline levels of select biomarkers significantly correlated with clinical response to treatment with BI 655064 at 12 wks. Disclosure of Interest: S. Visvanathan Employee of: Boehringer Ingelheim, M. Ramanujam Employee of: Boehringer Ingelheim, C. Schoelch Employee of: Boehringer Ingelheim, R. Vinisko Employee of: Boehringer Ingelheim, U. Mueller-Ladner Consultant for: Boehringer Ingelheim, S. Padula Employee of: Boehringer Ingelheim, J. Fine Employee of: Boehringer Ingelheim, J. Steffgen Employee of: Boehringer Ingelheim